Effects of the “Inspirational Lecture” in Combination With “Ordinary Antenatal Parental Classes” as Professional Support for Expectant Parents: A Pilot Study as a Randomized Controlled Trial - Thorstensson, Stina; Ekström-Bergström, Anette; Bäckström, Caroline (Frontiers in Public Health, 2020)
Background: Both expectant mothers and their partners describe weaknesses in ordinary parental preparatory professional support provided internationally and nationally within Sweden. Therefore, it is necessary to develop the parental preparatory professional support provided by midwives for expectant parents within Sweden. This study will evaluate the effects on expectant parents of receiving a combination of an “inspirational lecture” and “ordinary antenatal parental classes” compared with only “ordinary antenatal parental classes.” Methods/Design: This block randomized controlled trial included an intervention as a pilot study, in which expectant parents were randomized for 1) the inspirational lecture and ordinary antenatal parental classes (intervention group [IG]) (n = 66) or 2) ordinary antenatal parental classes (control group [CG]) (n = 60). Data collection with repeated questionnaires was conducted in the first week and six months after birth. Statistical analyses were conducted for participant characteristics, differences between parents within IG and CG, effects of the intervention, intention-to-treat, and internal consistency of the included measurements. Results: The intervention showed a tendency to be gainful for one out of four outcomes related to birth experience, and parents’ perceived quality of parental couple relationship consensus and sexuality and manageability. These results were more prominent for the partners. Parents within both the intervention and control groups reported decreased social support in the first six months after birth. Conclusion and clinical implications: Overall, the concept of the inspirational lecture in combination with ordinary antenatal parental classes as parental preparatory professional support seems to be a valuable care intervention. However, this study was a pilot study and the results should therefore be interpreted with caution. More research is needed since childbirth and transition to parenthood are complex processes in need of comprehension.